PERANCANGAN APLIKASI PENGELUARAN DAN PEMASUKAN BARANG - Bagas Dwi Cahyo; Ruben Zorsa Ferdianto; Silmi Kaafah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The development of information technology, especially software, in the last fifteen years has had a lot of influence on human life. This writing contains the application of expenditure and entry of product goods on the CV. Bonita Art & Paint. The author will explain how to work in payroll on the CV. Bonita Art. The author uses the PHP programming language in the use of payroll applications to assist in calculating employee salaries, compared to the complicated manual method, by using PHP, making reports on expenses and income of goods is easy and not complicated.